A study on the use of communicative translation method in English-Vietnamese public sign translation - Nguyen, Phuong Thi Lan (Penerbit Universiti Kebangsaan Malaysia, 2024)
This paper explores the use of the Communicative Translation Method (CTM) in translating public signs from English to Vietnamese. To fulfil this objective, two research methods are employed, including discourse analysis, which helps to analyse linguistic components used in the two texts and translation comparative, which helps to compare the linguistic and semantic similarities and differences between the source text and the target text to identify the use of CTM. A research sample consisting of 42 pairs of signs classified into five groups based on their functions is used for the analysis. The research findings indicate that CTM is the most popular method in the English-Vietnamese translation of public signs. Three specific techniques of CTM are used for the translation, including the omission of words from the translated text, the addition of words to the target signs and the adjustment of forms of expression in the target text. The research findings go in line with the proposals and descriptions of Newmark about CTM and the findings of previous studies, thereby further consolidating the theories related to translation methods in general and CTM in particular. Some implications on using CTM for informative texts in general and public signs, in particular, are provided to practitioners.